Role of autophagy in angiogenic potential of vascular pericytes - Milani, Soheil Zamen; Rezabakhsh, Aysa; Karimipour, Mohammad; Salimi, Leila; Mardi, Narges; Narmi, Maryam Taghavi; Sadeghsoltani, Fatemeh; Valioglu, Ferzane; Rahbarghazi, Reza (Frontiers in Cell and Developmental Biology, 2024)
The vasculature system is composed of a multiplicity of juxtaposed cells to generate a functional biological barrier between the blood and tissues. On the luminal surface of blood vessels, endothelial cells (ECs) are in close contact with circulating cells while supporting basal lamina and pericytes wrap the abluminal surface. Thus, the reciprocal interaction of pericytes with ECs is a vital element in the physiological activity of the vascular system. Several reports have indicated that the occurrence of pericyte dysfunction under ischemic and degenerative conditions results in varied micro and macro-vascular complications. Emerging evidence points to the fact that autophagy, a conserved self-digestive cell machinery, can regulate the activity of several cells like pericytes in response to various stresses and pathological conditions. Here, we aim to highlight the role of autophagic response in pericyte activity and angiogenesis potential following different pathological conditions.